The moderating of technological adoption on financial literacy and international entrepreneur intention - I. M., Abdul Rashid; Syahril Iman, Faisal; Najuwa, Mohd Nasir; Wan Ahmad Fauzi, Wan Husain; Noraznira, Abd Razak; Noorazeela, Zainol Abidin; Irza Hanie, Abu Samah (Ital Publication, 2024)
Scholars have been and will likely remain interested in the study of entrepreneurial intention because of its importance to the development of numerous countries. The literature on entrepreneurial intention has addressed a wide range of subjects, with particular emphasis on the factors that influence entrepreneurial intention. However, the vast majority of these studies were conducted overseas. Since this topic always focuses on the agriculture sector when determining entrepreneurial purpose, the study targeted that industry. The purpose of this study is to examine the aspirations of young Malaysians to become international entrepreneurs. It especially aims to determine the relationship between each component of financial literacy (attitude, subjective norm, and perceived behavioral control) and technological adoption, as well as the effect of technological adoption on young people's ambitions to become international entrepreneurs. The study's conclusions demonstrated that financial literacy (attitude, subjective norm, and perceived behavioral control) and youth international entrepreneur intention were mediated by technology adoption. The study's findings contribute to the body of knowledge and support the executive branch and other decision-makers' creation of policies and programs.